Magnetic transitions in exotic perovskites stabilized by chemical and physical pressure. Issue 15 (16th March 2020) - Ma, Yalin; Molokeev, Maxim S.; Zhu, Chuanhui; Zhao, Shuang; Han, Yifeng; Wu, Meixia; Liu, Sizhan; Tyson, Trevor A.; Croft, Mark; Li, Man-Rong
Abstract : Exotic perovskite Ca2− x Mn x MnTaO6 (0 ≤ x ≤ 1.0) stabilized by chemical and physical pressure adopts cationic-disordered Pbnm structure and exhibits a ferromagnetic to antiferromagnetic transition around x = 0.2. Abstract : Exotic perovskites significantly enrich materials for multiferroic and magnetoelectric applications. However, their design and synthesis is a challenge due to the mostly required recipe conditions at extremely high pressure. Herein, we presented the Ca2− x Mn x MnTaO6 (0 ≤ x ≤ 1.0) solid solutions stabilized by chemical pressure assisted with intermediate physical pressure up to 7 GPa. The incorporation of Mn 2+ into the A-site neither drives any cationic ordering nor modifies the orthorhombic Pbnm structure, namely written as (Ca1− x /2 Mn x /2 )(Mn1/2 Ta1/2 )O3 with disordered A and B site cationic arrangements. The increment of x is accompanied by a ferromagnetic to antiferromagnetic transition around x = 0.2, which is attributed to the double-exchange interactions between A-site Mn 2+ and B-site Mn 3+ . Partial charge disproportionation of the B-site Mn 3+ into Mn 2+ and Mn 4+ occurs for x above 0.8 samples as manifested by X-ray spectrum and magnetic behaviors. The coexistence of B-site Mn 3+ (Jahn–Teller distortion ion) and B′-site Ta 5+ (second-order Jahn–Teller distortion ion) could be energetically responsible for the absence of A-site columnar ordering as observed in other quadruple perovskites with half of the A-sites occupied by small transition-metal cations. These exceptional findings indicate that exotic perovskites can be successfully stabilized at chemical and intermediate physical pressure, and the presence of Jahn–Teller distortion cations at the same lattice should be avoided to enable cationic ordering.